Distribution of iron-titanium oxides in the vanadiferous main magnetite seam of the upper zone : Northern limb, Bushveld complex - Gwatinetsa, Demand (Rhodes University, Faculty of Science, Department of Geology, 2014)
The main magnetite seam of the Upper Zone of the Rustenburg Layered Suite (SACS, 1980) on the Bushveld Complex is known to host the world's largest vanadium bearing titaniferous iron ores. The vanadiferous titanomagnetites, contain vanadium in sufficient concentrations (1.2 - 2.2 per cent V₂O₅) to be considered as resources and vanadium has been mined historically by a number of companies among them Anglo-American, Highveld Steel and Vanadium and VanMag Resources as well as currently by Evraz Highveld Steel and Vanadium Limited of South Africa. The titanomagnetites contain iron ore in the form of magnetite and titanium with concentrations averaging 50-75 per cent FeO and 12-21 per cent TiO₂. The titaniferous iron ores have been historically dismissed as a source of iron and titanium, due to the known difficulties of using iron ore with high titania content in blast furnaces. The economic potential for the extractability of the titaniferous magnetites lies in the capacity of the ores to be separated into iron rich and titanium rich concentrates usually through, crushing, grinding and magnetic separation. The separatability of iron oxides and titanium oxides, is dependent on the nature in which the titanium oxide occurs, with granular ilmenite being the most favourable since it can be separated from magnetite via magnetic separation. Titanium that occurs as finely exsolved lamellae or as iron-titanium oxides with low titania content such as ulvospinel render the potential recoverability of titanium poor. The Upper Zone vanadiferous titanomagnetites contain titanium in various forms varying from discrete granular ilmenite to finely exsolved lamellae as well as occurring as part of the minerals ulvospinel (Fe₂TiO₄) and titanomagnetite (a solid solution series between ulvospinel and magnetite) . Discrete ilmenite constitutes between 3-5 per cent by volume of the massive titanomagnetite ores, and between 5-10 per cent by volume of the magnetite-plagioclase cumulates with more than 50 per cent opaque oxide minerals. The purpose of this research was to investigate the mineralogical setting and distribution of the iron and titanium oxides within the magnetitite layers from top to bottom as well as spatially along a strike length of 2 000m to determine the potential for the titanium to be extracted from the titanomagnetite ores. The titanomagnetites of the Upper Zone of the Bushveld Complex with particular reference to the Northern Limb where this research was conducted contains titanium oxides as discrete ilmenite grains but in low concentrations whose potential for separate economic extraction will be challenging. The highest concentration of titanium in the magnetite ores is not contained in the granular ilmenite, but rather in ulvospinel and titanomagnetite as illustrated by the marked higher concentration of TiO₂ in the massive ores which contain less granular ilmenite in comparison to the disseminated ores which contain 3 to 8 percentage points higher granular ilmenite than the massive ores. On the scale of the main magnetite seam, the TiO₂ content increases with increasing stratigraphic height from being completely absent in the footwall anorthosite. The V₂2O₅ content also increases with stratigraphic height except for in one of the 3 boreholes where it drops with increasing height. The decrease or increase patterns are repeated in every seam. The titanomagnetites of the main magnetite seam display a variety of textures from coarse granular magnetite and ilmenite, to trellis ilmenite lamellae, intergranular ilmenite and magnesian spinels and fine exsolution lamellae of ulvospinel and ferro-magnesian spinels parallel to the magnetite cleavage. The bottom contact of the main magnetite seam is very sharp and there is no titanium or vanadium in the footwall barely 10cm below the contact. Chromium is present in the bottom of the 4 layers that constitute the main magnetite seam and it upwards decreases rapidly. In boreholes P21 and P55, there are slight reversals in the TiO₂ and V₂O₅ content towards the top of the magnetite seams.
Keywords: Igneous rocks -- South Africa -- Bushveld Complex; Sulfide minerals -- South Africa -- Bushveld Complex; Vanadium -- South Africa -- Bushveld Complex; Titanium dioxide -- South Africa -- Bushveld Complex; Ferric oxide -- South Africa -- Bushveld Complex; Geology -- South Africa -- Bushveld Complex; Mineralogy -- South Africa -- Bushveld Complex; Mines and mineral resources -- South Africa